Development of Fluid Viscosity Coefficient Apparatus Based On jetAudio and Subtitle Edit - Haris Rosdianto; Emi Sulistri (STKIP Singkawang, 2020)
The purpose of this research was to develop a fluid viscosity coefficient apparatus using computer application that is easily obtained and used, namely jetAudio and Subtitle Edit software. The research was conducted at Physics laboratory in STKIP Singkawang and 5 secondary schools in Singkawang City. The feasibility level of this apparatus is known through validation by experts. Validation was carried out by 3 physics lecturers. The results of the validation stage were used for user tests by 10 STKIP Singkawang students. From the results of the analysis obtained 1) the results of validation by tool experts amounted to 91.1% which were interpreted very good, 2) the results of validation by material and content experts amounted to 91.9% which were interpreted very good, and 3) the results of user tests conducted by students showed the percentage of responses at 71.35% which was interpreted good. Thus the apparatus is feasible to use and can be an alternative in physics learning that can improve students' skills and conceptual understanding.